Editorial (2018)
Nowadays, society is characterized by complex systems, in which technology, ease of accessing information and even the increasing use of social networks have given way to new ideologies and subcultures; some of positivist line with univocal tendency and other postmodern, relativistic line, typical of equivocal hermeneutics, that make essential the generation of a critical and proactive conscience, that makes possible what in the words of the Dominican Mauricio Beuchot, is the existence of a hierarchy of approaches to a delimited or delimitable truth. In this sense, it is necessary to recognize the close relationship that exists between education and philosophy to develop, during the educational process, the strengthening of philosophical thinking that favors an educational praxis cohesive with the social fabric, without having the conception of  "the modern world is that of simulacra" , which, as Deleuze proposed with the principle of connection and heterogeneity, "any point can be connected to another, and it must be" ; that is, theory and practice cannot be separated from one another, they must always attend to and respond to a reality.Reality and its everydayness require reﬂection, because we cannot be indifferent to it, while also compelling an action, typical of the natural attitude of the human being, to question and try to answer their questions; as Aristotle put it, "all men naturally want to know.}". Therefore, the development of philosophical thinking, seeks to generate a scenario to respond to new problems and questions, considering cultural diversity, its plexus of values, languages and ideologies.Bauman afﬁrms that "our time, the time of cultural pluralism, as distinct from plurality of cultures, is not the time of nihilism" , it is important that the educational process is strengthened in a way that stimulates critical reﬂection, a function of philosophy, devalued in the current consumer society; this, reﬂected in the search for momentary satisfaction, providing answers that end in relativism or materialism. It must then return to the anthropological vision of the role of philosophy in education, which contemplates man in an integral way, without reductionism, encompassing the totality of life, and leading him to act in an ideal of freedom In the thinking of Paulo Freire, to achieve an authentically liberating education, it is necessary to make and live the dynamism of the philosophical spirit in education, without the need for biased information, rather requires to be intermingled with reality, where educational knowledge facilitates dialogue, as a method of transforming what is considered the oppressive cause . In this sense, education and philosophy go unfailingly together, this is how knowledge and science can be considered as a product of the interaction and implication between the philosophical reﬂection of the subject and reality , what Dewey deﬁnes as pragmatic philosophy , referring to the intentionality of the student to know, which is motivated from the interaction with the environment.The Magazine Quaestiones Disputatae - Topics in Debate, once again, presents the results of research processes, with the purpose of contributing to the construction of scientiﬁc knowledge in the ﬁeld of humanities and social sciences, in this opportunity, addressing various topics that invite to the reﬂection and analysis about the importance of teaching philosophy and its contributions to social reality.